Enhancing Educational Strategies for Sustainable Tourism in the Geopark Area: A Case Study Geopark Maros Pangkep - Andi Muhammad Yusuf Randy; Haryadi Darmawan; Sutanto Leo (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
Tourist destinations in ecologically sensitive areas face significant challenges in balancing visitor management with conservation efforts. The Rammang-Rammang Karst Area in Maros District, part of the proposed UNESCO Global Geopark Maros-Pangkep, exemplifies these challenges. This study investigates current visitor management strategies in Rammang-Rammang, focusing on physical, regulatory, economic, and educational approaches. Methodologically, the research employs a qualitative descriptive analysis through a case study approach. Data collection includes on-site observations, interviews with key stakeholders such as local tourism authorities, Geopark management, community-based tourism groups, and tour guides, supplemented by document analysis. Triangulation of data ensures reliability and validity. Key findings highlight the effectiveness of existing strategies in managing visitor impacts on both the environment and local culture. Challenges identified include inadequate infrastructure and inconsistent enforcement of regulations. Educational initiatives show promise in raising visitor awareness but require enhancement. The study concludes by recommending integrated strategies that strengthen regulatory frameworks, improve infrastructure, and enhance visitor education to achieve sustainable tourism practices in Rammang-Rammang. This research contributes insights applicable to similar karst landscapes globally, emphasizing the need for tailored approaches that harmonize conservation goals with socio-economic benefits. By addressing these challenges comprehensively, this study aims to support the long-term sustainability and resilience of ecotourism in Rammang-Rammang and comparable geological formations worldwide.